Genetic control of estrogen‐regulated transcriptional and cellular responses in mouse uterus. Issue 5 (31st January 2013) - Wall, Emma H.; Hewitt, Sylvia C.; Liu, Liwen; Rio, Roxana del; Case, Laure K.; Lin, Chin‐Yo; Korach, Kenneth S.; Teuscher, Cory
Abstract : The uterotropic response of the uterus to 17β‐estradiol (E2 ) is genetically controlled, with marked variation observed depending on the mouse strain studied. Previous genetic studies from our laboratory using inbred mice that are high [C57BL/6J (B6)] or low [C3H/HeJ (C3H)] responders to E2 led to the identification of quantitative trait (QT) loci associated with phenotypic variation in uterine growth and leukocyte infiltration. The mechanisms underlying differential responsiveness to E2, and the genes involved, are unknown. Therefore, we used a microarray approach to show association of distinct E2 ‐regulated transcriptional signatures with genetically controlled high and low responses to E2 and their segregation in (C57BL/6J×C3H/HeJ) F1 hybrids. Among the 6664 E2 ‐regulated transcripts, analysis of cellular functions of those that were strain specific indicated C3H‐selective enrichment of apoptosis, consistent with a 7‐fold increase in the apoptosis indicator CASP3, and a 2.4‐fold decrease in the apoptosis inhibitor Naip1 ( Birc1a ) in C3H vs. B6 following treatment with E2 . In addition, several differentially expressed transcripts reside within our previously identified QT loci, including the ERα‐tethering factor Runx1, demonstrated to enhance E2 ‐mediated transcript regulation. The level of RUNX1 in uterine epithelial cells was shown to be 3.5‐fold greater in B6 compared to C3H. Our novel insights into the mechanisms underlying the genetic control of tissue sensitivity to estrogen have great potential to advance understanding of individualized effects in physiological and disease states.—Wall, E. H., Hewitt, S. C., Liu, L., del Rio, R., Case, L. K., Lin, C.‐Y., Korach, K. S., Teuscher, C. Genetic control of estrogen‐regulated transcriptional and cellular responses in mouse uterus. FASEB J. 27, 1874–1886 (2013). www.fasebj.org